2016
DOI: 10.1111/cogs.12365
|View full text |Cite
|
Sign up to set email alerts
|

Preadolescents Solve Natural Syllogisms Proficiently

Abstract: "Natural syllogisms" are arguments formally identifiable with categorical syllogisms that have an implicit universal affirmative premise retrieved from semantic memory rather than explicitly stated. Previous studies with adult participants (Politzer, 2011) have shown that the rate of success is remarkably high. Because their resolution requires only the use of a simple strategy (known as ecthesis in classic logic) and an operational use of the concept of inclusion (the recognition that an element that belongs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…In the broader context of cognitive science on reasoning, can the result that topo-spatial representations were effective in reasoning with multiple quantifiers provide some more general implications? The findings of effective expression of tasks can contribute to task naturalisation in the psychology of reasoning (Politzer, Bosc-Miné & Sander, 2017). If the aim of the current research is measuring people's actual logical (not puzzle solving) capability, tasks involving inference, as opposed to just interpretation, should be set for participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the broader context of cognitive science on reasoning, can the result that topo-spatial representations were effective in reasoning with multiple quantifiers provide some more general implications? The findings of effective expression of tasks can contribute to task naturalisation in the psychology of reasoning (Politzer, Bosc-Miné & Sander, 2017). If the aim of the current research is measuring people's actual logical (not puzzle solving) capability, tasks involving inference, as opposed to just interpretation, should be set for participants.…”
Section: Discussionmentioning
confidence: 99%
“…9 Our experiment suggests that single quantifiers should be expressed as spatial relations and multiple quantifiers as topological relations, rather than both types being expressed as topological relations. However, according to Politzer et al (2017), natural tasks of categorical syllogism consist of one premise rather than two premises. This setting is realised by the fact that the existing knowledge of meaningful terms used in the statements can bridge the gap of an unstated premise.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore in the park, all the roses are frozen (Politzer et al, 2017(Politzer et al, , p. 1040 The three main differences between the abstract problem in (1) and the ecologically valid problem in (2) are: (i) the content of the premises, (ii) the inclusion in a context that renders the syllogism somewhat relevant and, (iii) the omission of one of the premises (here, all roses are flowers), which is taken as part of the participant's background knowledge (syllogisms with such an implicit premise are called enthymematic). These ecologically valid syllogisms significantly improved participants' performance, allowing 11-year-olds to perform as well as adults, and significantly better than same-age children on less ecologically valid versions of the same syllogisms (Politzer et al, 2017).…”
Section: And Marie Repliedmentioning
confidence: 99%
“…These studies, which used tasks that appear closely related to the control condition of Politzer et al (2017), have found instead activity in a lateral frontoparietal network that includes the posterior parietal cortex, the inferior and middle frontal gyrus, and the rostrolateral prefrontal cortex (Prado, Chadha, & Booth, 2011). Thus, this literature provides relatively little support for the idea that argumentative reasoning involves the mPFC or other regions involved in ToM.…”
Section: And Marie Repliedmentioning
confidence: 99%
See 1 more Smart Citation